FEATURES OF PROFESSIONAL FORMATION OF FUTURE TEACHERS OF ART SUBJECTS AESTHETIC CYCLE - Yu.V. Lokaryeva (Academy of Cognitive and Natural Sciences, 2004)
The article investigates the present today situation in terms of professional preparation of a future teacher as well as ways of effectively enhancing students' professionalism at the art teachers department.